Numidum massiliense gen. nov., sp. nov., a new member of the Bacillaceae family isolated from the human gut - M. Tidjani Alou; T.-T. Nguyen; N. Armstrong; J. Rathored; S. Khelaifia; D. Raoult; P.-E. Fournier; J.-C. Lagier (New Microbes and New Infections, 2016)
Numidum massiliense gen. nov., sp. nov., strain mt3T is the type strain of Numidum gen. nov., a new genus within the family Bacillaceae. This strain was isolated from the faecal flora of a Tuareg boy from Algeria. We describe this Gram-positive facultative anaerobic rod and provide its complete annotated genome sequence according to the taxonogenomics concept. Its genome is 3755739 bp long and contains 3453 protein-coding genes and 64 RNA genes, including eight rRNA genes.